Weibull Parameter Estimation Using Particle Swarm Optimization Algorithm - Gabriel Okafor, Ekene; Emmanuel Ezugwu, Okechukwu; Olugbeji Jemitola, Paul; Sun, Youchao; Lu, Zhong (International Journal of Engineering and Technology, 2018)
Many research works on Weibull parameter estimation has focused on graphical or analytical techniques, with little effort devoted towards the use of population based optimization algorithm. Accurate estimation of failure distributive parameter such as Weibull is a key requirement for efficient reliability analysis. In this study Particle Swarm Optimization Algorithm (PSOA), with particle position and velocity iteratively updated was used to estimate Weibull parameters. Probability density function and reliability plots were generated using the results obtained. Generally, PSOA shows better parameter estimation in comparison with analytical method based on Maximum Likelihood Estimator (MLE).Â Â